Correlation of tethered swimming with swimming performance - Morouço, P.; Soares, S.; Vilas-Boas, J. P.; Fernandes, R. (Archivos de medicina del deporte, 2008)
Tethered swimming aims to assess swimmers propulsive force (Magel, 1970), but its relationship with performance remains a matter of debate in the literature: some authors stands that it is a valid and reliable test (Kjendlie and Thorsvald, 2006) but others questioned it, mainly because arm and hand actions seem to differ (Maglischo and Maglischo, 1984). The purpose of the present study was to analyze the relationship between the force production assessed through a tethered swimming test and free swimming performance. Twelve male swimmers, of different competitive age-groups, of the Portuguese national team were studied: (i) group 1 - 6 swimmers (20.2±1.2 years; 179.3±12.1cm; 73.6±6.2kg) and (ii) group 2 - 6 swimmers (16.3±0.5 years; 181.0±5.4cm; 72.7±6.5kg). After a 1200m freely chosen warm-up, each subject performed a 30s maximum intensity front crawl tethered swimming test. Individual force to time - F(t) - curves were obtained in order to assess average pulling force in 30s (AvgF), average of all the maximum peak force values of each stroke cycle (MaxF) and average of all the minimum force values of each stroke cycle (MinF). Twenty-four hours later, swimmers performed a free swimming test in a long course pool: group 1 - 50m front crawl and group 2 - 200m front crawl. Time was registered in order to calculate average velocity of the 50m and 200m (v50m and v200m, respectively). In Figure 1 it is possible to observe an example of a curve representative of the tethered swimming test, showing the decrease of force production along the 30s effort. Additionally, in Table 1, the correlation values obtained between the studied variables (Pearson product moment) can be observed. AvgF, and MaxF, were highly correlated with all variables, obtaining both high values with v200m and v50m. These results point out that mean force (as well as maximal force) calculated in 30s maximal tethered front crawl can be considered as a good indicator of the ability to perform short and middle distance front crawl stroke events. The results seem also to indicate the possibility of the AvgF be able to be used to predict the mean velocity correspondent to a 50m front crawl (v = 0.004*tethered force + 1.331) and 200m front crawl (v = 0.004*tethered force + 1.208). In this sense, we encourage the use of the tethered swimming test as a useful toll for training control and evaluation of swimmers and, even, as a simple predictor of performance